The contribution of family climate and perceived emotional intelligence in promoting life satisfaction and reducing suicidal ideation among Spanish adolescents. - Peláez-Fernández, María Ángeles; Mérida-López, Sergio; Yudes Gómez, Carolina; Extremera-Pacheco, Natalio (My University, 2024)
Previous literature on the field has documented the association between emotional intelligence and life satisfaction and suicidal ideation among adolescents; however, few studies have investigated the moderating effect of family climate on the association. Thus, this study examined the moderating effect of family cohesion, expressiveness, and conflict on the relationship between emotional intelligence and life satisfaction and suicidal ideation among Spanish adolescents. A total of 2722 adolescents aged 12 to 18 (52.8% girls) participated in the study. The interaction effects were significant, with family conflict mitigating the effects of emotional intelligence on life satisfaction, and family cohesion and expressiveness strengthening the effects of emotional intelligence on suicidal ideation. These findings provide additional evidence for the protective role of family cohesion and expressiveness in adolescent suicidal ideation; and the harmful role of family conflict in adolescent well-being. Results imply that enhancing family cohesion and expressiveness and reducing family conflict may be a promising way to boost life satisfaction and prevent suicidal ideation among adolescents.
Keywords: Adolescentes - Psicología; Suicidio - Prevención; Madurez afectiva; Familia; Family climate; Emotional intelligence; Life satisfaction; Suicidal ideation; Adolescents